Zakat On Business Inventory: Issues And Challenges In Negeri Sembilan - Muhammad Aunurrochim Mas'ad Saleh; Muhammad Nurul Hasan bin Ruslan (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.